Spindle cell oncocytoma of the pituitary tumor: A rare case report and literature reviews - Chang, Chia Ning; Shen, Chiung Chyi (Frontiers in Surgery, 2023)
Introduction Spindle cell oncocytoma (SCO) of the pituitary gland is increasingly established with improvements in histological and immunohistochemical examination. However, the diagnosis was often mistaken based on imaging studies and nonspecific clinical manifestations. Purpose This case is presented to provide an overview of the characteristics of the rare tumor as well as to demonstrate the difficulties in diagnosis and current treatments. Clinical discussion The pathogenesis of SCO remains unclear, and a possible origin was described. Further research is needed to optimize pre-operative diagnosis and surgical strategy. Conclusion SCO should be considered when images indicate some features. Gross total resection (GTR) after surgery seems to have better long-term tumor control, and radiotherapy may help decrease tumor progression in patients with non-GTR. Regular follow-up is advised because of the higher recurrence rate.